Cardiovascular predictors of the post-COVID-19 course: results of a cohort study - V. I. Podzolkov; A. E. Bragina; A. I. Tarzimanova; I. I. Shvedov; E. S. Ogibenina; M. A. Avanesyan; A. S. Fomin (Российский кардиологический журнал)
Aim. To evaluate cardiovascular risk factors as predictors of the post-coronavirus disease 2019 (COVID-19) syndrome.Material and methods. This prospective cohort study included adult patients admitted to a university hospital with a clinically or laboratory-confirmed diagnosis of COVID-19. A number of cardiovascular risk factors were assessed at admission, including the Cardio-Ankle Vascular Index (CAVI). After hospital discharge, patients were observed for 6 months. Then, data on the course of the post-COVID-19 period was collected from electronic medical records and discharge summaries. Two following outcomes were assessed: the development of post-COVID-19 syndrome and the development of newly diagnosed diseases or worsening of existing chronic diseases in the post-COVID-19 period.Multivariable logistic regression was used to assess the association between potential predictors and outcomes, and odds ratios (OR) with 95% confidence intervals (95% CI) were calculated to assess the association strength. The statistical significance level was p<0,05.Results. The final analysis included 125 patients (68 (54,4%) women). The median age was 59,0 [50,5, 71,0] years. Post-COVID-19 syndrome was diagnosed in 32,8% of patients. The most common symptoms were weakness (19,2%), headaches (11,2%) and shortness of breath (10,4%). In multivariate analysis, CAVI ≥9,5, increased systolic blood pressure (SBP) and glomerular filtration rate (GFR) on admission were associated with the post-COVID-19 syndrome, with an OR of 2,415 (95% CI 1,174-2,846), 1,045 (95% CI 1,010-1,082), 0,971 (95% CI 0,946-0,998), respectively. Age (OR 1,056, 95% CI 1,009-1,105) and body mass index (OR 1,132, 95% CI 1,027-1,248) were associated with newly diagnosed diseases or worsening of existing chronic diseases in the post-COVID-19 period.Conclusion. Objective indicators such as SBP, CAVI and GFR may be predictors of post-COVID-19 syndrome, and age and body mass index are associated with the unfavorable course of chronic diseases in the post-COVID-19 period.